Business Design Of LPPD Platform At Pt. Telekomunikasi Indonesia Tbk Directorate Of Digital Business - Wiryatama, I Made Ardy; Chumaidiyah, Endang; Prambudia, Yudha (eProceedings of Engineering, 2023)
Abstract—Telkom Indonesia company's digital business directorate was developing digital solution applications. Among the tribes utilized as research objects is the smart city, which are solutions for the government named E-LPPD particularly in the implementation of government at the district, city, and provincial levels. E-LPPD aims to digitize the process to improvement. However, designing this business necessitates the study of various factors, including market factors, technical factors, and financial factors, which are covered in the business feasibility analysis and sensitivity analysis. The market analysis determines the estimated market demand for new, existing, and target markets. Business processes, company procedures, human resources, platform design in the form of prototype dashboards and mockups, and other components of information system design require technical considerations. In the financial element, which covers business feasibility study and sensitivity analysis, the net present value (NPV), payback period (PBP), and internal rate of return (IRR) are calculated (IRR). The company received an estimated market demand of 198 target markets throughout Indonesia. Based on the results, the business was viable, with a net present value (NPV) of Rp 216,231,494, an internal rate of return (IRR) of 18,8 percent, and a payback period (PBP) of 3 years and three months. Keyword—feasibility, sensitivity analysis, website design